Earthquake Damage Level of Gorontalo Area Based on Seismicity and Peak Ground Acceleration - Intan Noviantari Manyoe; Lantu .; Samsu Arif; Rakhmat Jaya Lahay (Jambura Geoscience Review, 2019)
Gorontalo is located at the macro and micro plate boundary, therefore it is located in an active seismotectonic region. This study aims to analyze earthquake damage level in Gorontalo based on seismicity and peak ground acceleration. The data used is obtained from the USGS. Data is made into a database and plotted onto a geological map. Calculation of peak ground acceleration is obtained using the Kawashumi formula. The results of this study indicate that Gorontalo is included in the slight to moderate earthquake damage level because it is dominated by shallow to intermediate earthquakes depth, light to moderate earthquake magnitude, and have a peak ground acceleration 1,462 - 99,714 gal.